Process Management for the Service Quality of an SME in the Gastronomic Sector (LACCEI, 2024)
The objective of the research was to determine the influence of the implementation of Process Management on the Quality of service of an SME in the gastronomic sector. The study was longitudinal, experimental, mixed. The population was 800 clients. A questionnaire validated by expert judgment and reliable (Cronbach's α of 0.855) was applied to 260 clients, an interview with the General Manager and non-participant observations were carried out at the company's facilities. The situation of the SME was diagnosed, through the Ishikawa diagram to know the problems of different areas and EFE matrix. The operational processes were diagrammed and documented, with their respective files and indicators. The result of the pretest was 58.40% and in the post test 65.40%, with a variation of 12% in customer satisfaction. The percentage of completion of the processes went from 66.17% in the pretest to 82.94% in the posttest, with an improvement of 25.34%. Through the Wilcoxon hypothesis test, it was determined that the Quality of Service of the company has a significant influence (p = 0.00 0.05) between before and after the Implementation of Process Management. The feasibility of the project was determined with an initial investment of S/.9 515, a NPV of S/. 14,254 an IRR of 71.1%, a B/C ratio of 1.84.